Pelatihan Penyusunan Surat Gugatan Mahasiswa/i Fasya-IAIN Fattahul Muluk Papua - Andryka Assagaf (Jurnal Pengabdian kepada Masyarakat Nusantara, 2022)
Indonesia has asserted itself as a constitutional state, and the legal adage has emphasized that where there is a community, there is the law (Ubi Societas Ibi Ius). With that also, in the interaction with the legal community is required to be commander in chief to resolve conflicts that arise from social interactions and various existing interests. Overcoming this requires legal knowledge along with the level of implementation of this knowledge, one of which is in the form of drafting a lawsuit. There is an assumption that drafting a lawsuit is difficult, so training in drafting a lawsuit is considered very important to carry out. This training is also a form of community service whose participants are IAIN Fattahul Muluk Sharia Faculty Students. In addition, the participants' knowledge was limited to general knowledge regarding procedural law and did not extend to technical knowledge. It is also hoped that this training can add new knowledge and hone the participants' skills in drafting a lawsuit so that the participants who will later hold a law degree already know the ins and outs of drafting a lawsuit.